Structural and electronic properties of Cs‐adsorbed GaN monolayer and bilayer based on first principles. (31st January 2021) - Liu, Lei; Tian, Jian; Lu, Feifei
Summary: A negative electron affinity photocathode can be obtained by adsorbing Cs on the emission layer surface of photocathode, which greatly improves the number of electrons escaped and the quantum efficiency. Based on first principles, this paper studies the structural and electronic properties of Cs‐adsorbed GaN monolayer and bilayer. The results reveal that the Cs‐adsorbed GaN monolayer is the most stable when Cs atom is adsorbed at TGa site. There is a significant charge transfer between Cs atom and GaN monolayer, and the difference in electronegativity makes electrons of Cs atom transfer to GaN monolayer system. Cs adsorption can reduce band gap, work function, and electron affinity, which is conducive to the escape of electrons and improvement of quantum efficiency. Cs adsorption is helpful for tuning optical properties of GaN monolayer. For the GaN bilayer, greater stability and lower work function make the Cs adsorbed above the top layer of GaN bilayer be more beneficial to the improvement of photoelectric performance. Novelty Statement: Based on first principles, this paper studies the structure and electric properties of Cs‐adsorbed GaN monolayer and bilayer. Cs adsorption can reduce band gap, work function, and electron affinity, which is conducive to the escape of electrons and improvement of quantum efficiency. And for the GaN bilayer, greater stability and lower work function make the Cs adsorbed above the top layer of GaN bilayer be more beneficial to the improvement of photoelectric performance. Abstract : Atomic structure and electric properties of Cs‐adsorbed GaN monolayer and bilayer layer are analyzed. When Cs atom is adsorbed at TGa site, Cs‐adsorbed GaN monolayer is the most stable. Electrons of Cs atom are transferred to GaN monolayer system because of difference in electronegativity. Cs adsorbed above the top layer of GaN bilayer is more beneficial to the improvement of photoelectric performance.